Awareness and Attitudes of the Pakistani Population With Regard to Physician–Pharmaceutical Company Interaction: A Cross-Sectional Study - Gillani, Ali Hassan; Omer, Sumaira; Arshad, Hafsa; Liu, Wenchen; Chen, Chen; Bashir, Sadia; Ahmed, Asma Bashir; Munir, Abubakar; Saeed, Amna; Bashir, Kamran; Fang, Yu (Frontiers in Pharmacology, 2022)
Objective: To determine the awareness and attitudes of the Pakistani population regarding physician–pharmaceutical company interactions. Methods The data were collected from primary health care clinics and pharmacy outlets located within cities of six randomly selected districts of the Punjab province. Those individuals (age ≥18 years) who just completed their visit to the physician and well understand both English and Urdu language were approached. Descriptive analysis was done for all variables by using SPSS (IBM version 26). Results: 3852 participants fully completed the study out of 4301(response rate 89.5%). Of those, 30.9% were female and 69.1% were male; two third (66.7%) were aware of drug representatives visits to clinics. The majority were aware of pharmaceutical company material presence (or absence) in the physicians’ room including drug company advertisements (56.6%), company items with logos (66.8%) and patient education materials (73.4%). 60.8% thought that receiving gifts from companies was ‘wrong/unethical’ practice for physicians, which was lower in comparison to other professions such as judges to accept gifts from lawyers (65.6%) and professional sports umpires to acknowledge gifts (64.3%). A minority showed lower trust on physicians for using drug company notepads or pens (16.7%), going on trips sponsored by the company (16.7%) and accepting gifts <15000 PKR (90.3US$) (26.7%). Trust was affected the most for accepting gifts >15000 PKR (90.3US$) (40.0%). Receiving free medication samples was associated with considering physicians’ acceptance of small gifts as ‘not a problem’. Conclusion: Survey participants were well aware of physician pharmaceutical company interactions. Participants were more knowledgeable regarding the pharmaceutical company presence (or absence) in physicians’ offices than about gift-related practices of physicians. Trust level was not affected for various types of interactions between physician drug companies, except for receiving large gifts